Primary Diffuse Large B Cell Lymphoma in Kidney with Involvement of Central Nervous System and Heart in a Siamese Cat - Chalfun Guimaraes-Okamoto, Priscylla Tatiana [UNESP]; Lopes da Silva, Maria Claudia [UNESP]; Sequeira, Julio Lopes [UNESP]; Hataka, Alessandre [UNESP]; Chacar, Fernanda Chicharo; Geraldes, Silvano Salgueiro [UNESP]; Antunes Ribeiro, Jose Francisco [UNESP]; Melchert, Alessandra [UNESP] (Univ Fed Rio Grande Do Sul, 2016)
Background: Lymphoma is the most common neoplasia in cats and usually happens in middle-aged males of European breeds, FeLV-positive test is also observed in 25% to 50% of these cases. The diagnostic of renal lymphoma is based on clinical signs, the diagnosis is based on clinical signs associated with additional tests. Histological and immunohistochemical evaluations allows the classification which can provide prognostic information. Central nervous system metastasis is frequently reported, but lingual and lung lobe extension were also reported. Here, we report a case of renal lymphoma with systemic involvement of heart and CNS in a cat. Case: A 3-year-old male Siamese cat presented with weight loss, emesis, anorexia, polydipsia and polyuria for at least 3 weeks. The clinical parameters were stable, but presenting pale mucosal membrane and also severe dehydration. Complete blood count and chemistry profile revealed anemia and severe azotemia. On abdominal palpation, bilateral renomegaly and irregular contours of both kidneys were also detected. The kidneys were enlarged and had irregular contours on palpation, confirmed by abdominal ultrasonography, that revealed kidneys with markedly irregular contours, and the presence of fluid with high cellularity between cortical and renal capsule (capsular fluid). An aspiration citology by fine-needle from the capsular fluid guided by ultrasound was collected and sent to cytological analysis, which suggested lymphoma. The aspirate was moderately cellular and consisted of large round cells with distinct, scant, basophilic cytoplasm, round nuclei with dense chromatin, inconspicuous nucleoli, and large amount of naked cells. On the second day of treatment the cat presented a cardiopulmonary arrest not responsive to cardiopulmonary cerebral resuscitation, died, and the owner authorized the necropsy, allowing the renal biopsy showing that the same neoplastic cells presented in kidneys were also seen in heart and central nervous system, suggesting the occurrence of primary renal lymphoma with involvement of to these tissues, and the diagnosis was high grade diffuse large cell lymphoma. And also histopathological exam diagnosed high grade diffuse large cell lymphoma. Discussion: The patient died, and the post-mortem histological analysis confirmed the diagnosis of primary diffuse large B cell lymphoma in kidney with systemic involvement of heart and central nervous system (CNS). Lymphoma is the most common renal tumor in cats, however primary feline renal tumors are rare and few reports are available at this time. Here we report the occurrence of primary renal lymphoma in a Siamese cat, and there's no previous report of this type of lymphoma especially in this breed. More investigation is needed to evaluate the susceptibility of Siamese cat breed to the development of primary renal lymphoma. It is difficult to determine whether the renal involvement is primary or it is a consequence of the multicenter type. In the present report the same neoplasic infiltration observed in kidney was also found in central nervous system and heart. The cytology is a quickly, non-invasive, and sensitivity method for the diagnostic of lymphoma. However, the cytology do not provides the immune diagnosis of diffuse large B cell, and although it is useful for staging lymphoma, histopathology and immunohistochemistry is always necessary for classification and grading. Since the diagnosis, the cat of this report survived only 2 days, which reinforces the bad prognosis of renal lymphoma. The renal lymphoma should be considered as a potential cause of severe azotemia, and should be taken as the mainly differential diagnosis among neoplasias of kidneys in cats.
Keywords: oncology; feline; extranodal; lymph nodes; cancer